Acquired Abdominal Intercostal Hernia: A Case Report and Literature Review - Salim Abunnaja; Kevin Chysna; Inam Shaikh; Giuseppe Tripodi (Case Reports in Surgery)
Acquired abdominal intercostal hernia (AAIH) is a rare disease phenomenon where intra-abdominal contents reach the intercostal space directly from the peritoneal cavity through an acquired defect in the abdominal wall musculature and fascia. We discuss a case of a 51-year-old obese female who arrived to the emergency room with a painful swelling between her left 10th rib and 11th rib. She gave a history of a stab wound to the area 15 years earlier. A CT scan revealed a fat containing intercostal hernia with no diaphragmatic defect. An open operative approach with a hernia patch was used to repair this hernia. These hernias are difficult to diagnose, so a high clinical suspicion and thorough history and physical exam are important. This review discusses pathogenesis, clinical presentation, complications, and appropriate treatment strategies of AAIH.